2020
DOI: 10.3390/s20092549
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Coils-Based Wireless Power Transfer for Intelligent Sensors

Abstract: Most wearable intelligent biomedical sensors are battery-powered. The batteries are large and relatively heavy, adding to the volume of wearable sensors, especially when implanted. In addition, the batteries have limited capacity, requiring periodic charging, as well as a limited life, requiring potentially invasive replacement. This paper aims to design and implement a prototype energy harvesting technique based on wireless power transfer/magnetic resonator coupling (WPT/MRC) to overcome the battery power pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…MRC also plays an essential role in heart rate sensors and cardiac monitoring. Mahmood et al [111] designed and implemented an MRC-WPT system using three different coil topologies (spiral-spiral, spider-spider, and spiral-spider) to supply power to a heart rate sensor. The design involves three parts: the power unit, which comprises the transmitter and receiver coils; the measurement component, which includes an Arduino Nano microcontroller and a heart rate sensor; and the nRF24L01 wireless protocol monitoring unit, as shown in Figure 12.…”
Section: Electrocardiograph Heart Rate and Cardiac Pressure Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRC also plays an essential role in heart rate sensors and cardiac monitoring. Mahmood et al [111] designed and implemented an MRC-WPT system using three different coil topologies (spiral-spiral, spider-spider, and spiral-spider) to supply power to a heart rate sensor. The design involves three parts: the power unit, which comprises the transmitter and receiver coils; the measurement component, which includes an Arduino Nano microcontroller and a heart rate sensor; and the nRF24L01 wireless protocol monitoring unit, as shown in Figure 12.…”
Section: Electrocardiograph Heart Rate and Cardiac Pressure Sensorsmentioning
confidence: 99%
“…The resonance frequency is 6.78 MHz. The results showed that the WPT FIGURE 12 (a) Spider-Spider magnetic resonant coupling wireless power transfer system at 20 cm proposed in [111] to measure heart rate. (b) Fabricated cardiac monitoring module (bottom view on the right and top view on the left) presented in [112].…”
Section: Electrocardiograph Heart Rate and Cardiac Pressure Sensorsmentioning
confidence: 99%
“…The resonator capacitors in the transmitter and receiver units are coupled in parallel with the L T and L R coils, respectively. The parallel-to-parallel compensation topology was chosen due to (i) facilitating higher power transfer between the two coils [28,29], (ii) it has a better performance than series-to-series topology in low power applications [30], where the proposed WHR consumes low power (≈0.166 W) and (iii) the ZVS oscillator (Xiongfaic Weiye Electronics Co., Ltd., Shenzhen, China) existing in our lab is restricted to the parallel topology and low oscillator frequency. The low frequency is suitable for using with parallel resonator topology, where the parasitic losses are reduced, while the series topology is more suitable for employing with high frequency [31].…”
Section: System Modelmentioning
confidence: 99%
“…On the other hand, active low power devices are basically logic gates acting like a switch and attached with sensors [50,51]. WSNs have different applications such as bio-medical [52,53], Internet of Things (IoT) [54], and environmental monitoring [55]. An ATS can run automatically with low power mode when it is required to sense the change in any parameter, processing the change in the form of the voltage signal, and transmitting that signal [56].…”
Section: Relation Between Electromagnetic Energy Harvesting and Autonomous Sensorsmentioning
confidence: 99%